Production and characterization of a monoclonal antibody for Pefloxacin and mechanism study of antibody recognition. Issue 4 (3rd April 2019) - Zhang, Xiuyuan; He, Kuo; Zhang, Donghao; Huang, Zhihong
ABSTRACT: In this report, an artificial antigen (PFLX–BSA: Pefloxacin connected bovine serum albumin) was successfully prepared. The monoclonal antibody against pefloxacin was produced and characterized using a direct competitive ELISA. The linear range of detection was 0.115–6.564 µg/L. The limit of detection defined as IC15 was 0.170 ± 0.05 µg/L and the IC50 was 0.902 ± 0.03 µg/L. The antibody variable region genes were amplified, assembled, and sequenced. A three–dimensional structural model of the variable region was constructed to study the mechanism of antibody recognition using molecular docking analysis. Three predicted essential amino acids, Thr53, Arg97 of heavy chain and Thr52 of light chain, were mutated to verify the theoretical model. Three mutants lost binding activity signiﬁcantly against pefloxacin as predicted. These may provide useful insights for studying antigen–antibody interaction mechanisms to improve antibody affinity maturation in vitro. Graphical abstract: : The dc-ELISA of IC15 was 0.151±0.07 ng/mL and IC50 was 0.891±0.03 ng/mL. Molecular docking analysis indicated that the Ser52, Thr53, Arg97, Tyr100, Leu51, Thr52, Ser53 amino acid residues played the decisive roles during recognition.